ANALISIS FAKTOR RISIKO PENULARAN PASIEN KUSTA - Rimbawati, Yazika; Wulandari, Ria (LPPM STIKes Mitra Adiguna, 2025)
Leprosy is one of the eight neglected tropical diseases that continues to pose a public health issue in Indonesia. This disease remains persistent and requires special attention. Several factors are associated with the incidence of leprosy, including BCG (Bacillus Calmette Guerin) vaccination status, contact history, duration of contact, personal hygiene, age, education level, knowledge, socioeconomic status, housing density, physical condition of the house, and gender (Hairil Akbar, 2020). The purpose of this study is to analyze the risk factors contributing to the transmission of leprosy among patients at the Lembak Community Health Center, Muara Enim Regency, in 2024. This research utilized a quantitative method with a cross-sectional approach, complemented by qualitative in-depth interviews to explore factors associated with leprosy transmission. The population consisted of all patients who sought treatment at the Lembak Community Health Center in 2023, totaling 62 individuals. The sampling method used was total sampling. The findings revealed a significant relationship between age (p-value = 0.015), genetic factors (p-value = 0.004), and socioeconomic status (p-value = 0.015) with leprosy transmission. This study concludes that age, genetic factors, and socioeconomic status significantly influence the transmission of leprosy. Thus, prevention and control measures should prioritize vulnerable age groups, individuals with a genetic predisposition, and populations with low socioeconomic conditions.